2017
DOI: 10.1038/ncb3499
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1–XPF cooperates with CTCF and cohesin to facilitate the developmental silencing of imprinted genes

Abstract: Inborn defects in DNA repair are associated with complex developmental disorders whose causal mechanisms are poorly understood. Using an in vivo biotinylation tagging approach in mice, we show that the nucleotide excision repair (NER) structure-specific endonuclease ERCC1-XPF complex interacts with the insulator binding protein CTCF, the cohesin subunits SMC1A and SMC3 and with MBD2; the factors co-localize with ATRX at the promoters and control regions (ICRs) of imprinted genes during postnatal hepatic develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 61 publications
(89 reference statements)
3
76
0
Order By: Relevance
“…Abrogation of XPG or XPF due to gene silencing or a mutation in their catalytic sites substantially hampers the recruitment of CTCF in chromatin, the formation of appropriate chromatin loops, and the fine tuning of RARb2 mRNA synthesis. In further support, a recent in vivo biotinylation tagging approach revealed that the heterodimer ERCC1–XPF complex interacts with CTCF, the cohesin subunits SMC1A and SMC3, and with MBD2 to facilitate the postnatal silencing of imprinted genes during murine development (Figure E) . Abrogation of ERCC1 in Ercc1 −/− mice or exposure of primary embryonic fibroblasts to the DNA interstrand cross‐linker mitomycin triggers the localization of CTCF to heterochromatin and the dissociation of the CTCF–cohesin complex and ATRX from promoters and imprinted control regions.…”
Section: Ner Factors and Chromatin Looping: The Ctcf Linkmentioning
confidence: 76%
See 3 more Smart Citations
“…Abrogation of XPG or XPF due to gene silencing or a mutation in their catalytic sites substantially hampers the recruitment of CTCF in chromatin, the formation of appropriate chromatin loops, and the fine tuning of RARb2 mRNA synthesis. In further support, a recent in vivo biotinylation tagging approach revealed that the heterodimer ERCC1–XPF complex interacts with CTCF, the cohesin subunits SMC1A and SMC3, and with MBD2 to facilitate the postnatal silencing of imprinted genes during murine development (Figure E) . Abrogation of ERCC1 in Ercc1 −/− mice or exposure of primary embryonic fibroblasts to the DNA interstrand cross‐linker mitomycin triggers the localization of CTCF to heterochromatin and the dissociation of the CTCF–cohesin complex and ATRX from promoters and imprinted control regions.…”
Section: Ner Factors and Chromatin Looping: The Ctcf Linkmentioning
confidence: 76%
“…Promoter recruitment occurred in the absence of any exposure to exogenous genotoxic insults and was sensitive to transcription inhibitors . Subsequently, ERCC1–XPF was shown to interact with multiple TFIID subunits, i.e., TATA‐associated factors and the TBP in vitro and in vivo and to assemble together with RNAPII and the basal transcription machinery at promoters of growth genes. In further support, the DNA repair‐deficient Ercc1 −/− animals share genome‐wide gene expression similarities with those of the transcription‐defective (but otherwise DNA repair‐proficient) Taf10 −/− mice .…”
Section: Linking Ner To Transcription Demandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, both senescent and HMGB2-knockdown cells are characterized by the dramatic clustering of CTCF foci into SICCs -this, in conjunction with the heterochromatic remodeling seen in senescence cells (but not upon HMGB2 knock-down), give rise to the strong reorganization seen in Hi-C data. Notably, such a stress-induced clustering was very recently observed in vivo in mice with deficient DNA repair mechanism (Chatzinikolaou et al, 2017). Inevitably, the differential regulation of additional chromatin-binding factors, like topoisomerase II (Uuskula-Reimand et al, 2016) or HMGB1, will also contribute to chromosome refolding in senescence.…”
Section: Discussionmentioning
confidence: 91%